Measuring instantaneous velocity in four swim strokes using an automatic head tracking system: a comparison study - Scott, M.; Elsworthy, N.; Elipot, M.; Brackley, V.; Kean, C. O. (ISBS Proceedings Archive (Michigan), 2023)
This study compared instantaneous swimming velocity from an automated video-based system to a tethered speedometer. Twenty-two state- and national-level swimmers (7 M, 15 F; 14.5 ± 2.5 yrs) swam 25 m of each stroke at maximal intensity. Bland-Altman plots showed good agreement between systems for backstroke and freestyle but poorer agreement for butterfly and breaststroke. The RMS error was also lower in backstroke and freestyle compared to butterfly and breaststroke. The differences in systems may be explained by the different body segments tracked by each system (head vs hips) and with differences being more apparent during butterfly and breaststroke due to the wave-like motion of these strokes. While the automated video-based system is suitable for measuring instantaneous swimming velocity, coaches, sports scientists, and swimmers should be aware of larger discrepancies between systems when assessing butterfly and breaststroke.